~*alphAOmega*~
New member
- Joined
- Sep 2, 2006
- Messages
- 5
lol just got back to school, beginning to get the math cogs into gear again :wink: so was just scrolling through some problems and got completly dumbfounded doing this sum :-
2^(X+1) + 2^(X - 1) = 320
what i did was i used the laws of exponents to make 2^(x + 1) into 2^X * 2
and 2^(X - 1) into 2^X * 1/2 ( as 2^-1 = 1/2^1)
so it comes out like
(2^X * 2) + (2^X * 1/2) = 320
now im stuck... :?
2^(X+1) + 2^(X - 1) = 320
what i did was i used the laws of exponents to make 2^(x + 1) into 2^X * 2
and 2^(X - 1) into 2^X * 1/2 ( as 2^-1 = 1/2^1)
so it comes out like
(2^X * 2) + (2^X * 1/2) = 320
now im stuck... :?